Satisfied Generation Y Parents Spread Good Recommendations: Satisfaction, Service Quality, and Brand Trusts Impact on Word of Mouth in International Education - Stribbell, Howard; Duangekanong, Somsit (วารสารวิชาการ การจัดการภาครัฐและเอกชน, 2022)
This article aimed 1) to determine how service quality, parent satisfaction and brand trust affects the likelihood of parents to recommend the international school to family and friends and 2) to test the mediating role of parent satisfaction. The research model was quantitative research and adds to the research body regarding K12 international schools. The sample group was 425 Generation Y parents whose children attend The International School of Macao. The parents completed on a contextually relevant and reliable survey in English or Chinese. The results were analyzed uses SPSS and AMOS to develop a structural equation model. The research findings were 1) parent satisfaction had the largest impact on the likelihood of parents to recommend the school through word of mouth. Parent perception of service quality and brand trust had an impact on satisfaction. 2) satisfaction fully mediates the relationship between service quality and word of mouth and partially mediates the relationship between brand trust and word of mouth. The findings from this research fills a gap in research in K12 international schools and informs school administrators of the importance of fulfilling parent satisfaction to affect school recommendations from parents.